PEMANFAATAN WHATSAPP SEBAGAI MEDIA KOMUNIKASI ANTARA DOSEN DAN MAHASISWA DALAM MENUNJANG KEGIATAN BELAJAR (Studi terhadap Mahasiswa UIN Imam Bonjol Padang) - Afnibar Afnibar; Dyla Fajhriani (Universitas Islam Negeri Imam Bonjol Padang, 2020)
WhatsApp is an online media that is widely used by students and lecturers. WhatsApp application can provide convenience in interacting and communicating. Through this application can add more friends, making it easier for users to get to know each other and as a media to support learning activities. This research aims to determine the use of whatsapp as a medium of communication between lecturers and students in supporting learning activities. The research method used is quantitative research. The data source is 53 students from Imam Bonjol Padang. This research is a survey, through the Google form media. The results revealed that, students feel that what makes it easier to communicate and support learning activities compared to other online media was obtained by 23 people (43.40%) choosing statements often, and as many as 16 people (30.20%) stated always. It can be interpreted that most of the students (73.60%) felt that it was easier for them to communicate and support learning activities compared to other online media. Furthermore, more than 70% of students stated that the application of whatsApp had a positive impact on their learning activities and supported the improvement of their communication with lecturers. So, whatsApp is one of the media that has benefits including facilitating communication and supporting learning activities. The ease in using whatsApp makes students feel helped by this application and becomes one of the important and preferred means of communication for students